4-H Agent Guide for Managing the Approval, Denial, and Releasing of Volunteers in Florida 4-H - Andrew Toelle; Heather Kent; Sophia Cooney (EDIS, 2022)
The purpose of these Volunteer Management Guidelines is to provide Extension faculty assistance with approving, denying, and releasing volunteers. This document contains several example letters that may be used and other useful tools to assist you with this process. It also demonstrates steps in approving, denying, and releasing volunteers. Written by Andrew Toelle, Heather Kent, and Sophia Cooney; 7 pp. https://edis.ifas.ufl.edu/4h428